ANALISIS 8-ISOPROSTAN DALAM URIN TIKUS JANTAN WISTAR SETELAH TERPAPAR ETANOL DAN ASAP ROKOK - Ari Chandra Wibawa, Agung; Suaniti, Ni Made; Ariati, Ni Komang (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014, 2014)
The 8-isoprostane compound can be used for a biomarker of oxidative stress  formed by lipid peroxidation in the form of arachidonic acid with free radical in the body. The purpose of this study was to analysis  urinary 8-isoprostane in male Wistar rats after sub-acute exposer to ethanol and cigarette smoke. Extraction method used was solid phase extraction and the analysis was conducted by TLC and spectrophotodensitometry. The results showed that the 8-isoprostane compound was not detected in the male Wistar rat’s urine as control rats and in those exposed to cigarette smoke. The average concentrations of 8-Isoprostane in the male Wistar rat’s urine exposed to ethanol and combination of ethanol-cigarette were 1.519 ± 1,386 and 2.063 ± 1,308 ppm respectively.
Keywords: 8-isoprostane, Arachidonic acid, TLC, Spectrophotodensitometry